A hegzapodic herpetic dendritic ulcer developing on the background of band keratopathy - Ozalp, Onur; Atalay, Eray; Yildirim, Nilgun (Digital Journal of Ophthalmology, 2019)
A 40-year-old man presented emergently at Eskişehir Osmangazi University Hospital with a penetrating scleral injury. The perforation was repaired surgically. During the follow-up period the patient developed a retinal detachment, and he underwent pars plana lensectomy and vitrectomy with silicone oil injection. Three years postoperatively he presented with complaints of redness, burning, and stinging in his eye. Biomicroscopic examination showed a dendritic lesion superimposed on band keratopathy of the corneal surface. Herpes keratitis was suspected, and the patient was started on valacyclovir 1 g orally, ganciclovir gel 5 times daily, cyclopentolate eye drops 3 times daily, and artificial tears. The herpetic lesion regressed on the 10th day of follow-up, but the cornea was not fully reepithelialized. Manual superficial keratectomy and double amniotic membrane transplantation were performed to accelerate epithelization, and the patient’s clinical symptoms regressed after systemic, topical, and surgical treatment. Oral valacyclovir (500 mg) prophylaxis was initiated, and there was no recurrence at 1 year’s follow-up.